Pengaruh Implementasi Asi International Financial Reporting Standard dalam Rangka Indeks Gray Leverage terhadap Pengungkapan Laporan Keuangan - Efrianti, Desi; ., Yanto (Jurnal Ilmiah Akuntansi Kesatuan, 2017)
Disclosure of financial statements is a mean of delivering information by the company’s internal to stakeholders outside of the company. On this globalization era, IASC (International Accounting Standard Committee) tries to create a custom standard for all in order to financial statement can be understood by all users in different countries, and so the IFRS (International Financial Reporting Standard) is published. It certainly brings a big impact on accounting study in Indonesia. One of those is about convergence of IFRS into PSAK as base of financial reporting as one form of disclosure to stakeholders outside of the company. This study was conducted to obtain empirical evidence about the effect of the implementation IFRS on the disclosure of financial statements as measured by leverage in this case the Gray index. The populations in this study are all listed banks in Indonesia Stock Exchange for the period of 2009-2014. Sample was 30 banking firms selected using purposive sampling method with predetermined criteria. Independent variable is in the form of leverage Gray index. Analysis used in this study is a descriptive analysis and simple linear regression analysis with SPSS as tool for calculation. The result showed the implementation of IFRS in the leverage Gray index has no effect on financial disclosure. Conclusions of the research are implementation of IFRS itself has effect on the financial disclosure but Gray index leverage has no significant effect under the IFRS standards. Result from t-test value is -0.122 and smaller than t-table value of 2.048. Thus, the variable of Gray index leverage is not recommended to be used to measure the width of financial reports disclosures under the standards of IFRS. There are still many aspects to be studied to determine the effect of accounting standards using other representations of company characteristics.